Pemanfaatan Teknologi AI dalam Pembelajaran IPA Di Sekolah Dasar - Hayati Mida Rongan; Markhamah Markhamah; Masduki Masduki (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the utilization of Artificial Intelligence (AI) in science learning at the elementary school level, including its forms of implementation, the role of teachers, student responses, challenges, and its impact on the learning process. This research employed a descriptive qualitative approach conducted at SD Muhammadiyah 7 Surakarta. The research participants consisted of the principal, a fifth-grade teacher, and 25 fifth-grade students. Data were collected through observations, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data reduction, data display, and conclusion drawing. The findings revealed that AI was utilized through adaptive learning applications, educational chatbots, instructional videos, and automated assessment tools. Teachers played a role as facilitators and guides in the use of AI technology. Most students demonstrated increased motivation, enthusiasm, and engagement in science learning. However, the implementation of AI still faced challenges related to limited infrastructure, technology access, and teachers’ digital competencies. Overall, the use of AI had a positive impact on students’ understanding of science concepts, learning motivation, and the quality of learning interactions. The study concludes that AI has significant potential to improve the quality of science learning in elementary schools, provided that it is supported by teacher readiness, adequate technological infrastructure, and supportive educational policies.